FT-Raman Spectroscopy of Heavy Metal-Nucleotide Complexes - IYANDURAI, N.; SENTHIL, K.; SAROJINI, R. (Asian Journal of Chemistry, 2010)
FT-Raman spectroscopic study was made on an interaction between deoxyguanosine 5'-monophosphate (dGMP) and Cd2+ and Cu2+ in an aqueous solution with various metal ion concentrations. The spectrum reveals that both the ions bind to the phosphate groups. The spectral changes observed for the vibrations of deoxy ribose moiety near 844 cm-1 in Cd-dGMP complexes shows that the C2'-endo/anti conformation is completely eliminated at higher concentration (r = 1) whereas in Cu-dGMP complex the glygosyl bond shows more flexibility. Spectral changes are also observed for the guanine base vibration and the mode of interaction is discussed in detail.